Adherence to antiretroviral treatment (ART) among HIV-infected pregnant women starting treatment immediately vs delayed: a cohort study - Langwenya, Nontokozo (Department of Public Health and Family Medicine, 2017)
Introduction: Use of highly effective antiretroviral drugs to eliminate new paediatric HIV infections is the keystone of all prevention of mother-to-child transmission (PMTCT) programmes. Time on antiretroviral treatment (ART) before delivery reduces maternal viral load and decreases the risk of transmission in utero, during labour and whilst breastfeeding. Currently, many PMTCT programmes across Africa initiate HIV-infected pregnant women on lifelong antiretroviral therapy (ART) on the first day of antenatal care ("same-day" initiation). However concerns have been raised regarding patient readiness and whether same-day initiation in pregnancy may contribute to subsequent ART non-adherence. Methods: As part of a larger study of ART in pregnancy, consecutive ART-eligible pregnant women making their first antenatal care (ANC) visit at a primary care facility in Cape Town, South Africa were enrolled into a prospective cohort between March 2013 and June 2014. Before July 2013, eligibility was based on CD4 cell count ≤350 cells/μL ("Option A"), with a 1-2 week delay from the first ANC visit to ART initiation; thereafter all women were eligible regardless of CD4 cell count ("Option B+") and typically offered ART on the same day as first ANC visit. All women received standardized counselling before starting a fixed-dose regimen. Study interviews were conducted separately from the ART service through one week postpartum with self-reported adherence from 30- day recall. Results: Among 625 consecutive ART-eligible women (median age, 28 years; median gestation, 21 weeks; 55% newly diagnosed with HIV), 72% of women started ART same-day; this proportion was higher under "Option B+" versus "Option A" (p< 0.001). Of those with adherence assessments data available (n=618), 29% reported at least one missed ART dose during pregnancy. Missed doses were reported more frequently among women with previous use of PMTCT (p=0.014), of younger age (p=0.029) and starting ART under Option B+ (p=0.019). In women initiating ART same-day, 31% reported a missed dose compared to 23% among women who delayed ART start following first ANC visit (odds ratio, 1.07; 95% CI: 0.61 – 1.88). This finding did not vary after adjustment for demographic and clinical measures, and was consistent when restricted to women with CD4 cell counts ≤350 cells/μL. Conclusions: These results suggest same-day ART initiation in pregnant women is not associated with increased non-adherence during the antenatal period. While these results are reassuring for ART programmes implementing "Option B+", further research is required to examine adherence over time, particularly postpartum.